Association between Ala-9Val polymorphism of Mn-SOD gene and schizophrenia - Akyol, O; Yanik, M; Elyas, H; Namli, M; Canatan, H; Akin, H; Zoroglu, SS (Pergamon-Elsevier Science Ltd, 2005)
Reactive oxygen species (ROS) have been suggested to play an important role in physiopathology of schizophrenia. The major intracellular antioxidant enzymes, copper-zinc superoxide dismutase in the cytoplasm and manganese superoxide dismutase (Mn-SOD) in the mitochondria, rapidly and specifically reduce superoxide radicals to hydrogen peroxide. Polymorphisms in the genes encoding antioxidant enzymes should therefore result in predisposition to schizophrenia. The present study was performed to assess; whether there is a genetic association between a functional polymorphism (Ala-9Val) in the human Mn-SOD gene in schizophrenic patients (n=153) and healthy controls (n=196) using a PCR/RFLP method. Significant differences in the genotypic distribution between schizophrenics and controls were observed. Genotypic distribution with 14 (9.2%) Ala/Ala, 106 (69.3%) Ala/Val and 33 (21.6%) Val/Val subjects, in schizophrenia was different from those of controls with 46 (23.5%), 83 (42.3%) and 67 (34.21/6), respectively (p<0.0001). When the patents with schizophrenia were divided into the subgroups as disorganized, paranoid and residual. there was a significant difference In genotypic distribution among the subgroups (chi(2)=11.35, df=4 p=0.023). This association between -9Ala Mn-SOD allele and schizophirenia suggests that -9Ala variant may have a contribution in the physiopathogenesis of schizophrenia. Further investigations are warranted in larger populations with other susceptible genes that might be associated with schizophrenia. (C) 2004 Published by Elsevier Inc.
Keywords: gene polymorphism; manganese superoxide dismutase; schizophrenia